CHANGES IN THE ORAL CAVITY AFTER ANTIMYCOBACTERIAL DRUGS IN PATIENTS WITH PULMONARY TUBERCULOSIS - Toshtemirova Mohira Mahmud qizi; Tulqinov Yashnar; Hamidov Mahmud Toshtemirovich (Western European Studies, 2024)
his study investigates the impact of antimycobacterial drugs on oral cavity changes in patients diagnosed with pulmonary tuberculosis. Pulmonary tuberculosis, a global health concern, necessitates prolonged treatment with antimycobacterial drugs. While the primary focus is often on the pulmonary effects of these medications, their potential influence on oral health has been a subject of growing interest. The research employs a comprehensive approach, combining clinical observation and patient-reported outcomes to elucidate alterations in the oral cavity induced by antimycobacterial therapy.
Keywords: Antimycobacterial drugs; oral cavity changes; pulmonary tuberculosis